Clean morphological features of fungi of types of Macrosporium tomato and Septoria Lycopersici var Licopersici (Experimental biology, 2016)
The article presents the research works on culture-morphological features of fungi species Macrosporium tomato and Septoria Lycopersici var Licopersici, affecting vegetable seeds. Was allocated fungi Septoria Lycopersici var licopersici, Macrosporium tomato in pure culture.
Keywords: macrosporiosis; septoriosis; pycnidium; conidium; suspensios; Licopersicon еsculentum; Septoria licopersici var licopersici; Macrosporium tomato; Daucus carota.